ANALISIS PERAN DISIPLIN KERJA DOSEN PENDIDIKAN PANCASILA BERDASARKAN PERSEPSI MAHASISWA UNIVERSITAS MADURA - Aristin, Rini; Hasbullah, Hasbullah; Firdaus, Sukma Umbara Tirta; Azizah, Rina Nur; Kasanova, Ria (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the role of work discipline of lecturers teaching Pancasila Education courses at the University of Madura based on student perceptions. Lecturer work discipline is an important factor that affects the quality of the learning process and student motivation in attending lectures. This study uses a descriptive approach with an in-depth study of five lecturers who teach in various faculties, namely the Faculty of Administrative Sciences, the Faculty of Education, the Faculty of Law, the Faculty of Engineering, and the Faculty of Agriculture. Data was collected through in-depth interviews and observations, then analyzed thematically to identify patterns and meanings of student experiences related to lecturers' work disciplines. The results of the study show that lecturers' work discipline includes punctuality, material readiness, responsiveness to students, and consistency in evaluation which directly impacts learning effectiveness. Student perceptions confirm that disciplined lecturers motivate them to be more active and serious in participating in the learning process. Although there are obstacles such as administrative burdens that affect the consistency of lecturer discipline, lecturers' commitment to work discipline still has a significant positive impact. This study recommends that educational institutions provide adequate support to lecturers in managing workload and developing policies that encourage the implementation of optimal work discipline. Further studies are suggested to expand the scope of the sample and use data triangulation to gain a more comprehensive understanding of the factors that affect lecturers' work discipline and their impact on the quality of education.